2018
DOI: 10.1007/s00425-018-03081-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of brassinosteroids and influence of 24-epibrassinolide with brassinazole on their content in the leaves and roots of Hordeum vulgare L. cv. Golden Promise

Abstract: Main conclusion 24-epibrassinolide overcame the inhibitory effect of brassinazole on the barley growth and the content of brassinosteroids. The present work demonstrates the occurrence of mainly castasterone, brassinolide and cathasterone and lower amounts of 24-epibrassinolide, 24-epicastasterone, 28-homobrassinolide, typhasterol, 6-deoxocastasterone and 6-deoxotyphasterol in 14-day-old de-etiolated barley (Hordeum vulgare L. cv. Golden Promise). We also investigated the endogenous level of brassinosteroids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…These results are similar to the studies of Janeczko and Swaczynova [ 49 ], who demonstrated the increases of endogenous content of BL and CS in wheat ( Triticum aestivum ) seedlings treated with 0.1 µM EBL. The stimulatory effect of 0.1 µM EBL on the level of BRs in barley ( Hordeum vulgare ) was also reported [ 48 ].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…These results are similar to the studies of Janeczko and Swaczynova [ 49 ], who demonstrated the increases of endogenous content of BL and CS in wheat ( Triticum aestivum ) seedlings treated with 0.1 µM EBL. The stimulatory effect of 0.1 µM EBL on the level of BRs in barley ( Hordeum vulgare ) was also reported [ 48 ].…”
Section: Discussionmentioning
confidence: 85%
“…Similarly to the growth rate, the most increase of BRs’ level was reported under the influence of 0.1 µM BL, while during the treatment with 1 µM BL, the content of BRs declined. These BRs’ level alterations may be associated with the direct effect of exogenously applied BRs on their biosynthetic pathways [ 48 ]. Furthermore, the application of BL to hydroponically cultured duckweed influenced the considerable absorption of BL manifested in the increases of its endogenous level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brz decreased the level of BRs in the barley leaves, but not in roots. The inhibition effect of Brz on plant growth is reversed by exogenous BR ( Bajguz and Asami, 2004 ; Bajguz and Asami, 2005 ; Bajguz et al., 2019 ).…”
Section: Inhibitors Of Br Biosynthesismentioning
confidence: 99%